Partial loss of function of colony‐stimulating factor 1 receptor in a patient with white matter abnormalities. (3rd April 2018) - Konno, T.; Miura, T.; Harriott, A. M.; Mezaki, N.; Edwards, E. S.; Rademakers, R.; Ross, O. A.; Meschia, J. F.; Ikeuchi, T.; Wszolek, Z. K.
Abstract : Background and purpose: Mutations in colony‐stimulating factor 1 receptor ( CSF1R ) cause adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP). Patients with ALSP can be misdiagnosed as having acute ischemic stroke due to hyperintensity lesions on diffusion‐weighted magnetic resonance imaging. Mutant CSF1R proteins identified in ALSP show a complete loss of autophosphorylation of CSF1R. Methods: We conducted mutation screening of CSF1R in 123 patients with definite acute ischemic cerebrovascular syndrome and positive family history of stroke. The pathogenicity of identified variants was evaluated using functional analyses. The levels of autophosphorylation of CSF1R in response to treatment with ligands of CSF1R were examined in cells transfected with wild‐type and mutant CSF1R. Results: We identified eight CSF1R variants, six were known non‐pathogenic polymorphisms, whereas the other two were missense variants inducing substitution of amino acid residues (p.Glu573Lys and p.Gly747Arg). Functional assay showed that the levels of autophosphorylation of p.Gly747Arg were similar to those of wild‐type when treated with ligands. The autophosphorylation of p.Glu573Lys was detectable, but significantly decreased compared with those of wild‐type CSF1R ( P < 0.001, two‐wayanova with Bonferroni). The clinical presentation of the patient with p.Glu573Lys was consistent with cerebral embolism. The patient did not have typical clinical findings of ALSP. However, periventricular white matter abnormalities, unrelated to the recent infarct, were evident on brain magnetic resonance imaging. Conclusions: In contrast to ALSP‐associated missense mutations, CSF1R p.Glu573Lys variant in a patient with acute ischemic cerebrovascular syndrome showed a partial loss of autophosphorylation of CSF1R; its clinical significance warrants further investigation.